CONCEPTUAL METAPHOR AS MEANS OF TEACHING ENGLISH SPEECH PATTERNS IN HIGHER EDUCATION - Matsevich, Svetlana; Korenetskaya, Irina; Kuzmichenko, Anna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The article focuses on the relevant problem of finding new methods in theory and practice of teaching foreign languages and attempts an interdisciplinary research of conceptual metaphors both as a phenomenon of linguistics and English-language training. The authors view the research novelty in considering conceptual metaphors of educational discourse as one of the means of teaching students English speech patterns. The research aim is to identify basic conceptual metaphors of educational discourse and describe the algorithm of using them in teaching English at universities. The primary methods of the study are conceptual-taxonomic analysis and the Metaphor Identification Procedure (MIP). The materials of the study include the articles of the English-language educational discourse and topical lectures on Education, Communication, Science and Society at TED Talks platform. The main research results present conceptual metaphor classification and its possible use as the means of teaching English speech patterns. The basic mechanism of learning new English speech patterns through conceptual metaphors suggests the implementation of cognitive-communicative approach. The results of the research are addressed to master and post-graduate students when learning English in professional sphere of education sciences.